Neglected fungal zoonoses: hidden threats to man and animals. (May 2015) - Seyedmousavi, S.; Guillot, J.; Tolooe, A.; Verweij, P.E.; de Hoog, G.S.
Abstract: Zoonotic fungi can be naturally transmitted between animals and humans, and in some cases cause significant public health problems. A number of mycoses associated with zoonotic transmission are among the group of the most common fungal diseases, worldwide. It is, however, notable that some fungal diseases with zoonotic potential have lacked adequate attention in international public health efforts, leading to insufficient attention on their preventive strategies. This review aims to highlight some mycoses whose zoonotic potential received less attention, including infections caused by Talaromyces ( Penicillium ) marneffei, Lacazia loboi, Emmonsia spp., Basidiobolus ranarum, Conidiobolus spp. and Paracoccidioides brasiliensis .